Pathological and sonographic review of early isolated severe lower urinary tract obstruction and implications for prenatal treatment. (1st April 2022) - Vinit, N.; Bessières, B.; Spaggiari, E.; Heidet, L.; Gubler, M.‐C.; Dreux, S.; Attie‐Bitach, T.; Blanc, T.; Ville, Y.
ABSTRACT: Objective: To identify favorable renal histology in fetuses with early severe lower urinary tract obstruction (LUTO) and determine the best timing and selection criteria for prenatal surgery. Methods: This multicenter, retrospective study included male fetuses with severe LUTO which died before 24 weeks of gestation during the period January 2000 to December 2018. Age‐matched controls were used as reference standard for renal histology. Prenatal ultrasound features and fetal serum and/or urine β 2microglobulin level were retrieved and kidney histology slides (hematein‐eosin‐safran and α ‐smooth‐muscle‐actin ( α SMA) immunostaining) were prepared and reviewed. α SMA‐positive staining of the blastema is due to its aberrant differentiation into myofibroblastic cells. Cases were sorted into histopathologic groups (favorable or unfavorable) according to the blastema's morphology and α SMA labeling and the data of these groups were compared. Results: Included in the study were 74 fetuses with a median gestational age at outcome of 17 + 6 (range, 13 + 0 to 23 + 5) weeks. Parenchymal organization was preserved in 48% of the kidneys. A blastema was present in 90% of the kidneys, but it was morphologically normal in only 9% and α SMA‐negative in only 1% of them. Most (82%) fetuses had an unfavorable prognosis, and 36% of fetuses died ≤ 18 weeks and had severe renal lesions detected on histology (early unfavorable prognosis). A favorable renal prognosis was associated with an earlier gestational age ( P = 0.001). Fetuses with LUTO had a significantly lower number of mature glomeruli ( P < 0.001) compared with controls. However, there was no significant difference in the number of glomeruli generations between the early‐unfavorable‐prognosis group (≤ 18 weeks) and the group with a favorable prognosis ( P = 0.19). A comparison of prenatal ultrasound features and biochemical markers between groups could not identify any prenatal selection criteria. Conclusions: Before 18 weeks, around 30% of fetuses with severe LUTO still have potential for kidney development. Identification of these cases would enable them to be targeted for prenatal therapy. © 2021 International Society of Ultrasound in Obstetrics and Gynecology.